Nucleotides in both donor and acceptor splice sites are responsible for choice in NAGNAG tandem splice sites - Hujová, Pavla; Souček, Přemysl; Radová, Lenka; Kramárek, Michal; Kováčová, Tatiana; Freiberger, Tomáš (Cellular and molecular life sciences, 2021)
Among alternative splicing events in the human transcriptome, tandem NAGNAG acceptor splice sites represent an appreciable proportion. Both proximal and distal NAG can be used to produce two splicing isoforms differing by three nucleotides. In some cases, the upstream exon can be alternatively spliced as well, which further increases the number of possible transcripts. In this study, we showed that NAG choice in tandem splice site depends considerably not only on the concerned acceptor, but also on the upstream donor splice site sequence. Using an extensive set of experiments with systematically modified two-exonic minigene systems of AFAP1L2 or CSTD gene, we recognized the third and fifth intronic upstream donor splice site position and the tandem acceptor splice site region spanning from -10 to +2, including NAGNAG itself, as the main drivers. In addition, competition between different branch points and their composition were also shown to play a significant role in NAG choice. All these nucleotide effects appeared almost additive, which explained the high variability in proximal versus distal NAG usage.
Keywords: alternativní sestřih; tandemové repetitivní sekvence; exony; NAG choice; Humans; HeLa buňky; místa sestřihu RNA; Tandem Repeat Sequences; RNA splicing; Exons; lidé; nukleotidy; Alternative Splicing; Nucleotides; Alternative splicing; Splicing isoform; HeLa Cells; AFAP1L2; nádorové buněčné linie; Introns; Cell Line, Tumor; RNA Splice Sites; introny